Epidemiological profile of blood donors with sickle cell trait in the State of Piauí, Brazil (Research, Society and Development, 2021)
The study presented here aims to discuss social and demographic variables of blood donors with variant hemoglobins in the state of Piauí, in 2019, through the analysis of data collected from them and stored in HEMOVIDA. The data obtained were subjected to statistical analysis using the SPSS program, in which they were crossed and the proportions were compared using the Χ2 test. According to the results obtained, of the 37840 donors, 1666 tested positive for variant hemoglobins, 1376 (3.64%) of whom had the sickle cell trait. Most donors (79.3%) live in the city of Teresina, 46.1% were between 19 and 29 years old and the most mentioned professional occupation was that of a student, 22.8% of the total. In addition, 64.8% of donors reported being single. When the gender variable was observed, 57.75% were men, with these also presenting the majority of cases of sickle cell trait. Regarding race, there was no statistical difference when comparing the numbers of individuals with variant hemoglobins, which goes against the studies highlighted in the literature. This paper discusses the race variable critically, understanding that the mechanisms of ethnic recognition are crossed by a complex web of relationships in a colonized society, which may be behind this discrepancy. Patients with the falsiform trait also reported less education compared to donors with HbAA hemoglobins.